2016
DOI: 10.1111/hae.13089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the utility of the ISTHBAT in haemophilia carriers: a multinational study

Abstract: Our results show that haemophilia carriers experience abnormal bleeding, including haemarthrosis. Overall, BS in women with Type 1 VWD > haemophilia carriers > Type 3 VWD OC > controls. Understanding the performance of the ISTH-BAT in this population is a critical step in future research aimed at investigating the underlying pathophysiology of abnormal bleeding, with the ultimate goal of optimizing treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(124 citation statements)
references
References 20 publications
5
118
1
Order By: Relevance
“…11,12 WGH represent the second largest group of women with inherited blood clotting defects after patients with von Willebrand disease (VWD). 6,7,14 Despite the fact that the haemorrhagic phenotype of WGH with reduced clotting factor activity has been reported in literature to resemble that of mild haemophilia patients and that the recommended treatment is the same, 2 to our knowledge, this was the first study that directly compared WGMH and males with mild haemophilia. 6,7,14 Despite the fact that the haemorrhagic phenotype of WGH with reduced clotting factor activity has been reported in literature to resemble that of mild haemophilia patients and that the recommended treatment is the same, 2 to our knowledge, this was the first study that directly compared WGMH and males with mild haemophilia.…”
Section: Discussionmentioning
confidence: 95%
“…11,12 WGH represent the second largest group of women with inherited blood clotting defects after patients with von Willebrand disease (VWD). 6,7,14 Despite the fact that the haemorrhagic phenotype of WGH with reduced clotting factor activity has been reported in literature to resemble that of mild haemophilia patients and that the recommended treatment is the same, 2 to our knowledge, this was the first study that directly compared WGMH and males with mild haemophilia. 6,7,14 Despite the fact that the haemorrhagic phenotype of WGH with reduced clotting factor activity has been reported in literature to resemble that of mild haemophilia patients and that the recommended treatment is the same, 2 to our knowledge, this was the first study that directly compared WGMH and males with mild haemophilia.…”
Section: Discussionmentioning
confidence: 95%
“…4,13 Most subjects in our study were scored for menorrhagia based on their high frequency of sanitary napkin changes, at less than every 2 hours. Specific to China, the Chinese healthcare system is mostly hospital-centred and the delivery system is Heterogeneity between different cultural populations might also play a part in our observation that both our carriers and control females had a higher prevalence of menorrhagia than were observed in earlier reports.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] A number of studies have clearly demonstrated increased bleeding tendency in haemophilia carriers compared to controls, with cutaneous bleeding, heavy menstrual bleeding and excessive/prolonged bleeding after invasive procedures and childbirth being the most common. [2][3][4] A number of studies have clearly demonstrated increased bleeding tendency in haemophilia carriers compared to controls, with cutaneous bleeding, heavy menstrual bleeding and excessive/prolonged bleeding after invasive procedures and childbirth being the most common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is promising in terms of efficiently generating useful data that reflects the bleeding severity experienced by these women, which should make the assessment of bleeding in haemophilia carriers more widely accessible. Interestingly, the sensitivity for the identification of a low FVIII/FIX level is higher for the Self‐BAT than for the ISTH‐BAT, where it was 57% in haemophilia carriers . The population studied with the ISTH‐BAT was more diverse; recruited from 7 centres throughout North American, Europe and South Africa, perhaps explaining the difference.…”
Section: Includes Information On All Haemophilia Carriers Enrolled (Nmentioning
confidence: 99%